2007
DOI: 10.1016/j.jeconom.2006.10.017
|View full text |Cite
|
Sign up to set email alerts
|

The size distribution of innovations revisited: An application of extreme value statistics to citation and value measures of patent significance

Abstract: This paper focuses on the analysis of size distributions of innovations, which are known to be highly skewed. We use patent citations as one indicator of innovation significance, constructing two large datasets from the European and US Patent Offices at a high level of aggregation, and the Trajtenberg (1990) dataset on CT scanners at a very low one. We also study self-assessed reports of patented innovation values using two very recent patent valuation datasets from the Netherlands and the UK, as well as a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(104 citation statements)
references
References 18 publications
6
97
0
1
Order By: Relevance
“…This approach is original, as most studies use exogenously fixed (identical across years and technologies) criteria to distinguish between breakthrough and regular innovations instead, by defining breakthroughs as the patents belonging to the top 5% or top 1% quantiles of the citations distributions. The statistical properties that spurred the initial application of the method were highlighted by SILVERBERG and VERSPAGEN (2007). They showed that a lognormal distribution fits most of the forward citations distribution for patents quite well, except for the tail: the numbers of received citations of highly cited patents rather follow a Pareto distribution.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This approach is original, as most studies use exogenously fixed (identical across years and technologies) criteria to distinguish between breakthrough and regular innovations instead, by defining breakthroughs as the patents belonging to the top 5% or top 1% quantiles of the citations distributions. The statistical properties that spurred the initial application of the method were highlighted by SILVERBERG and VERSPAGEN (2007). They showed that a lognormal distribution fits most of the forward citations distribution for patents quite well, except for the tail: the numbers of received citations of highly cited patents rather follow a Pareto distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Empirical examination of patent data shows that Pareto distributions are superior at matching the observed frequency distributions in the right tail of the distribution of the 'value' of innovations (SCHERER et al, 2000), also when the value is measured with the numbers of citations received by patents (SILVERBERG and VERSPAGEN, 2007).…”
Section: Appendix A: Use Of Hill Estimators To Identify Superstar Patmentioning
confidence: 98%
See 2 more Smart Citations
“…As discussed by Nešlehova, Embrechts & Chavez-Demoulin (2006), tail indices less than one are observed for empirical loss distributions of a number of operational risks. Furthermore, Scherer, Harhoff & Kukies (2000) and Silverberg & Verspagen (2004) report the tail indices α to be considerably less than one for financial returns from technological innovations. Rachev et al (2005) discuss and review the vast literature that supports heavy-tailedness and Pareto distributions for equity and bond returns.…”
Section: Introductionmentioning
confidence: 99%